(untitled) - Mr. Irfan Ullah Khan; Beenish Naz; Mubashir Ahmad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Salt and Saffron by Kamila Shamsie resents the compendium confused accurate appraisal of tradition, change, and nationalism that has relevance to division, disjunctive differences, and globalisation. In Salt and Saffron, the commemorative narrative indicates postcolonial effects and connections; reconfiguration with identity transformation, pre-partition and pre-colonial transfers are shown. Aliya's life illustrates the migrant's identity, global citizenship, feministic viewpoints of worlding, and self-adjustment in an Americanized culture. The relationship between glocalization, globalisation, and national consciousness has demonstrated the underlying verisimilitude. The narrative's characters depict the current acceleration and conventional ideas in relation to postcolonial viewpoints. In Salt and Saffron, the reconciliation of appropriation and abrogation in contemporary postcolonial power relations is described. In addition, the contextualization of the narrative is examined in order to provide a new positioning for persistence and emerging family dichotomous perspectives and evaluations. This study is qualitative in nature only. Through Orientalism, Occidentalism, and diasporic experiences, this article analyses the underlying verisimilitudes. The adoption of a new identity, the rejection of parental beliefs, and the abhorrence of one's own cultural background and origins are explored in depth. Infrequently, the hegemonic cultural re-constructions obstruct the indigenized indigenous origins movement and displacement of postcolonial period multitudes. It has been examined that the new generation has a major link to global processes, cultural intelligences relevant to conventional inclinations, avenues for perplexity, and the submersion of the protagonist's reality in Alya's Salt and Saffron.